Ultrasound-Enhanced Latex Immunoagglutination and PCR as Complementary Methods for Non-Culture-Based Confirmation of Meningococcal Disease - Gray, Stephen J. (American Society for Microbiology, 1999)
Preadmission administration of antibiotics to patients with suspected meningococcal infection has decreased the likelihood of obtaining an isolate and has stimulated development of rapid and reliable non-culture-based diagnostic methods. The sensitivity of the conventional test card latex agglutination test (TCLAT) for detection of capsular polysaccharide has been reported to be suboptimal. In the United Kingdom meningococcal DNA detection by PCR has become readily available and is now used as a first-line investigation. Recently, the performance of latex antigen detection has been markedly improved by ultrasound enhancement. Three tests for laboratory confirmation of meningococcal infection, (i) PCR assays, (ii) TCLAT, and (iii) ultrasound-enhanced latex agglutination test (USELAT), were compared in a retrospective study of 125 specimens (serum, plasma, and cerebrospinal fluid specimens) from 90 patients in whom meningococcal disease was suspected on clinical grounds. Samples were from patients with (i) culture-confirmed meningococcal disease, (ii) culture-negative but PCR-confirmed meningococcal disease, and (iii) clinically suspected but non-laboratory-confirmed meningococcal disease. USELAT was found to be nearly five times more sensitive than TCLAT. Serogroup characterization was obtained by both PCR and USELAT for 44 samples; all results were concordant and agreed with the serogroups determined for the isolates when the serogroups were available. For 12 samples negative by USELAT, the serogroup was determined by PCR; however, for 12 other specimens for which PCR had failed to indicate the serogroup, USELAT gave a result. USELAT is a rapid, low-cost method which can confirm a diagnosis, identify serogroups, and guide appropriate management of meningococcal disease contacts. A complementary non-culture-based confirmation strategy of USELAT for local use supported by a centralized PCR assay service for detection of meningococci would give the benefits of timely information and improved epidemiological data.